Frequency Analysis for Rainfall Design in Medan North Sumatra Indonesia - Indri Triawati; Haishen Lü; Ali, Atif Muhammad; Habiburrahman, Novan; Palupi, Retno (Universitas Kristen Cipta Wacana, 2025)
Rainfall is an essential component of climatology that should be consistently analyzed over extended periods. Availability of complete rainfall data is one of the most important parts in relation to Hydrology and Water Resources. The ideal data is that in accordance with what is needed. However, in practice, incomplete records are often encountered, this can be caused by several things, including equipment damage, employee negligence, equipment replacement, and natural disaster. This situation causes certain parts of the time series data to contain empty data, it is necessary to pay attention to the pattern of the distribution of rain and the surrounding stations. In this paper, there are three rainfall stations analyzed, these are BBMKG Region I, Sampali station, and Belawan station. Unfortunately, there are two missing rainfall data in 2001 and 2006 in Belawan station. Therefore, this paper uses the Normal Ratio Method and the Inversed Square Distance Method to complete the rainfall data and compare the two methods. From the result, there are different values from the two methods, the value is smaller using the Normal Ratio Method. It can be caused by the influence of distance factors on inversed square distance.